2008
DOI: 10.1002/jmor.10602
|View full text |Cite
|
Sign up to set email alerts
|

Blubber morphology in wild bottlenose dolphins (Tursiops truncatus) from the Southeastern United States: Influence of geographic location, age class, and reproductive state

Abstract: This study investigated blubber morphology and correlations of histological measurements with ontogeny, geography, and reproductive state in live, wild bottlenose dolphins (Tursiops truncatus) from the southeastern United States. Surgical skin-blubber biopsies (N=74) were collected from dolphins during capture-release studies conducted in two geographic locations: Charleston, SC (N=38) and Indian River Lagoon, FL (N=36). Histological analysis of blubber revealed stratification into superficial, middle, and dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 52 publications
10
92
1
Order By: Relevance
“…1 and 3). These patterns are similar to those observed in other nonarctic cetaceans; notably, bottlenose dolphins from the southern United States (Struntz et al, 2004;Montie et al, 2008). Deep blubber samples consist of the smallest adipocyte populations.…”
Section: Stratification Of Bowhead Blubbersupporting
confidence: 81%
See 4 more Smart Citations
“…1 and 3). These patterns are similar to those observed in other nonarctic cetaceans; notably, bottlenose dolphins from the southern United States (Struntz et al, 2004;Montie et al, 2008). Deep blubber samples consist of the smallest adipocyte populations.…”
Section: Stratification Of Bowhead Blubbersupporting
confidence: 81%
“…In regard to structure, little variation in connective tissue, adipocyte size, and adipocyte number amounts were detected in more external blubber layers, whereas greater variations in these traits were seen in more inner layers of fin whale (Balaenoptera physalus), harbor porpoise (Phocoena phocoena), and bottlenose dolphin (Tursiops truncatus) blubber (Aguilar and Borrell, 1990;Koopman et al, 1996;Struntz et al, 2004). Biochemical stratification in lipid composition occurs in the blubber of harbor porpoises between external and internal blubber layers (Koopman et al, 1996).Taken together, these studies have identified that more internal blubber layers are closely associated with lipid utilization, whereas more external layers are less dynamic and fulfill a primarily insulative and biomechanical function (Ackman et al, 1965;Koopman et al, 2002;Mau, 2004;Struntz et al, 2004;Montie et al, 2008). Histological and biochemical blubber parameters are related to environmental conditions to formulate hypotheses about developmental and environmental correlates of morphology.…”
mentioning
confidence: 86%
See 3 more Smart Citations